The Global Persistence of Terrorism as a Non Traditional Security Threat in the Millennial Era - Romadhon, Aditya; Putri, Revi Jeane; Anshori, M. Wira; Ahmad, Zakly Hanafi; Pratama, Galank (Journal of Politics and Policy, 2025)
This literature review critically investigates the evolving nature of terrorism as a non-traditional security threat in the contemporary global system. Drawing upon recent literature and empirical data, this paper explores the ideological, technological, and geopolitical transformations that shape terrorism as a persistent, adaptable, and cross-border phenomenon. This review emphasizes the shift from politically motivated attacks to religious extremism, digital propaganda, and regional instability, particularly in Southeast Asia. Furthermore, it reveals how non-traditional security challenges, such as terrorism, have redefined national and regional policy agendas. It also highlights the role of regional cooperation, ideological narratives, and digital technology in counter-terrorism strategies.